When Electoral Decentralization Fails: Elite Capture and the Limits of Welfare Governance in Indonesia - Sugiantiningsih, Anak Agung Putu; Gusmao, Fernando Dias; Hidayaturrahman, Mohammad; Jailani, Safiruddin (Journal of Governance and Public Policy, 2026)
Direct regional elections have been widely recognized as a cornerstone of Indonesia's democratic decentralization, expanding political participation and strengthening the electoral legitimacy of local governments. Nevertheless, evidence regarding their contribution to public welfare remains inconclusive. Existing studies have primarily examined electoral competitiveness and democratic participation, while paying limited attention to the mechanisms through which elite capture constrains welfare governance. This study investigates how direct regional elections shape welfare outcomes through the interaction between electoral competition, political patronage, and elite behavior after two decades of decentralization in Indonesia. Employing a qualitative comparative political analysis, the study draws on secondary data from the Central Statistics Agency (BPS), Bank Indonesia, the World Bank, government policy documents, and leading national media reports. The findings indicate that although direct elections have enhanced democratic participation and political legitimacy, welfare improvements remain uneven across regions. High campaign costs, patronage networks, and short-term electoral incentives encourage political elites to prioritize political survival over long-term development strategies, thereby weakening welfare governance. The study identifies an electoral governance paradox in which expanded democratic participation coexists with persistent elite capture, limiting the translation of electoral legitimacy into measurable welfare outcomes. These findings contribute to the literature on democratic decentralization by demonstrating that electoral institutions alone are insufficient to improve welfare without stronger accountability mechanisms that constrain elite capture and align political incentives with long-term public welfare. Official website of these institutions and leading online media, such as Kompas, Tempo, and others. Results of the study indicate that the direct regional head elections failed to improve public welfare in the regions, and are busy recovering.